The newly emerged COVID-19 disease: a systemic review - Endeshaw Chekol Abebe; Tadesse Asmamaw Dejenie; Mestet Yibeltal Shiferaw; Tabarak Malik (2020)
Abstract Coronaviruses are large family-RNA viruses that belong to the order Nidovirales , family Coronaviridae , subfamily Coronavirinae . The novel COVID-19 infection, caused by a beta coronavirus called SARS-CoV-2 , is a new outbreak that has been emerged in Wuhan, China in December 2019. The most common symptoms of COVID-19 are fever, cough, and dyspnea. As per the March 12, 2020, WHO report, more than 125,048 confirmed COVID-19 cases and over 4613 deaths have been identified in more than 117 countries. It is now regarded as a pandemic that seriously spread and attack the world. The primary means of transmission is person to person through droplets that occurred during coughing or sneezing, through personal contact (shaking hands), or by touching contaminated objects. So far, there is no effective therapy and vaccine available against this novel virus and therefore, only supportive care is used as the mainstay of management of patients with COVID-19. The mortality rate of COVID-19 is considerable. This work aimed to provide insight on the newly emerged COVID-19, in the hope to gain a better understanding on the general overview, epidemiology, transmission, clinical features, diagnosis, treatment, and clinical outcomes as well as the prevention and control of COVID-19.